Cultural Identity and Digital Media Representation: A Study of Dev Anderson and Willow Williams in Simone Soltani's Cross the Line - Ahsan Dimasius; Y. B. Agung Prasaja (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the role of digital media in identity construction as represented in Simone Soltani's Cross the Line (2024), analyzed through Stuart Hall's Cultural Identity Theory. Employing a qualitative descriptive design with a literary and cultural studies approach, the research addresses three questions: what forms of identity construction appear in the novel, what factors shape identity construction in the digital era, and what impacts identity construction produces on the characters. Data collection produced a structured tabulation of all 335 pages of the novel, organized into clusters recording quotations, meanings, and interpretations. The analysis confirms that all seven forms of identity synthesized from Hall's theory being, becoming, representation, discursive, multiple, fragmented, and constantly negotiated are represented through the experiences of the two protagonists, Dev Anderson and Willow Williams. Seven identity-shaping factors are likewise confirmed, with media and digital representation emerging as the most distinctive force in the narrative. The impacts of identity construction are categorized into psychological, professional, and relational-social dimensions. The findings suggest that in the digital era, a person's identity is no longer separable from how they are represented online, and that protecting one's digital representation has become inseparable from protecting who one is allowed to be.